Pengaruh Earning Per Share (EPS) dan Stuktur Modal Terhadap Nilai Perusahaan - Fitri Nurhayati M; Zulkifli Bokiu; Nurharyati Panigoro (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This study aims to determine the Effect of Earning Per Share (EPS) and Capital Structure on Company Value both partially and simultaneously. The data used is secondary data in the form of financial statements of financing services sub-sector companies for 2017 – 2021 obtained from www.idx.co.id. The number of samples in this study amounted to 6 companies obtained by purposive sampling sample technique. Data analysis in this study used multiple linear regression analysis with the help of the E-Views program. The results showed that 1) Earnings per Share has a positive effect but not on Company Value, 2) Capital Structure has a positive effect but not on Company Value, and 3) Earning per Share and Capital Structure simultaneously have a but not significant effect on Company Value.